Internalisasi Nilai-nilai Ketuhanan menuju Insan Kamil dalam Perspektif Filsafat Islam - Veni Fauziyyah (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the internalization of divine values towards perfect human beings in the perspective of Islamic philosophy. This study uses a qualitative approach by applying a descriptive-analytical method. The formal object of this research is Islamic philosophy, while the material object is human beings. The results and discussion in this study indicate that human beings and their existence are part of the unity of the name and form of God as the nature and essence of themselves. This study concludes that there is an internalization of divine values towards humans who can be said to be perfect human beings after being examined using the view of Islamic philosophy. This study recommends that readers add to their knowledge about human beings and the attributes of God to get to know their religious teachings further.